Assessment of the hydrocarbon potential of the Crimean peninsula: state and prospects - R. O. Samsonov; M. Yu. Karpushin; O. V. Krylov; A. A. Suslova; T. O. Kolesnikova; A. N. Stafeev; R. S. Sautkin; E. A. Krasnova; Ya. A. Shitova (Georesursy, 2024)
The active development of the Crimean region requires the provision of an independent energy system. Currently, there are 36 hydrocarbon fields in Crimea: 12 with natural gas, 9 with oil, 4 with oil and gas, 2 with oil and gascondensate and 9 gascondensate fields (according to www. mygeomap.ru portal by February 10, 2023). Despite the fact that the vast majority of fields are small and some of them werealready under the development it is necessary to consider their potential and production possibility at least for selling products on the domestic market within Crimea peninsula. In the second half of the last century, extensive exploration work was almost completely stopped because small deposits in the drilled structures have been found. Most of the traps of the Mezocenozoic section are complicated bythe faults. The possibility of discovering unexplored yet hydrocarbon resources especially in the lower stratigraphic complexes can be solved due to modern technologies distribution in the area. The contribution of deeper Permian-Triassic and Jurassic complexesto of modern hydrocarbon accumulations formation is poore evaluated and need to be analyzed in more details. Proper setting of geological exploration tasks and conducting modern regional and local seismic surveys will significantly increase the possibility of discovering new hydrocarbon deposits.